Gambaran Tingkat Pengetahuan Ibu Hamil tentang Tanda Bahaya Preeklampsia - Jumriani Jumriani; Putri Yayu; Nurbaety Nurbaety (Jurnal Sehat Mandiri, 2026)
Preeclampsia is one of the leading causes of maternal mortality and remains a major public health problem in Indonesia, which can be prevented through early detection. The level of knowledge among pregnant women regarding the danger signs of preeclampsia is an important factor in preventing complications. This study aimed to determine the level of knowledge of pregnant women about the danger signs of preeclampsia at the Tobelo Public Health Center, North Halmahera Regency. This study used a quantitative descriptive design with a cross-sectional approach. The sample consisted of 50 pregnant women selected using total sampling technique. Data were collected using a questionnaire and analyzed univariately in the form of frequency distribution and percentages. The results showed that the majority of respondents were aged 20–35 years (74%), had a secondary level of education (62%), and were multigravida (72%). The level of knowledge of pregnant women about the danger signs of preeclampsia was mostly in the moderate category (54%), followed by low (26%) and good (20%). These findings indicate that the knowledge of pregnant women is still not optimal in recognizing the danger signs of preeclampsia. Therefore, it is necessary to improve health education through antenatal care (ANC) services to enhance pregnant women’s understanding in early detection of pregnancy complications and to reduce the risk of maternal and neonatal morbidity and mortality.